Comparative Analysis of Rainfall Patterns in Jatigede Watershed Using the Huff Method - Setiyowati, Yunita Ayu; Harisuseno, Donny; Sajali, M. Amar (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
The temporal distribution of rainfall plays a vital role in hydrological analysis, particularly in estimating peak flood discharge, which significantly impacts the design of flood control infrastructure. Understanding rainfall distribution patterns is essential for improving flood forecasting and water resource management. This study aims to compare the rainfall distribution patterns in the Jatigede Watershed (DAS Jatigede) using the Huff Quartile 1 to 4 method. Hourly rainfall data were collected from six rainfall stations: Bayongbong, Cikajang, Darmaraja, Jatigede, Leuwigintung, and Sadawangi, with Ground Station data used for validation. The analysis revealed that rainfall in the Jatigede Watershed is steeper than Huff Quartile 1, with peak intensity occurring earlier during events, indicating a high concentration of rainfall at the beginning of storms, which may affect flood peak formation and watershed response time. These findings underscore the need to adjust hydrological models to better reflect actual rainfall distribution. However, the study has limitations, including a relatively small number of observation stations, potential inaccuracies in rainfall measurements, and the Huff method’s limited ability to capture spatial rainfall variability. Addressing these limitations in future research is essential for enhancing flood risk assessment and hydrological modeling accuracy in the Jatigede Watershed.